COMORBIDITIES WITH THE HIGH RISK OF DEATH AMONG COVID-19 PATIENTS: LEARNING FOR INDONESIA - Mahdiyyah Husna Nihar; Muhammad Atoillah Isfandiari (Jurnal Berkala Epidemiologi, 2022)
Background: In general, the entire population is vulnerable to COVID-19, but epidemiological research shows that the elderly and people with comorbid are more susceptible to COVID-19 and has a high risk of experiencing poor outcomes and death if infected with COVID-19. Purpose: This study aims to identify comorbidities with a high risk of death common among COVID-19 patients in China and the United States to provide learning for Indonesia in COVID-19 management. Methods: The literature review method was done by searching relevant articles through Google Scholar and ScienceDirect. Inclusion criteria are all original research and case series containing epidemiological information and comorbidities in COVID-19 patients aged >19 years with full text and open access. Exclusion criteria are study COVID-19 concerning children and adolescents (≤19 years) and study without comorbidities information. There is no language selection because all articles found are in English. Results: There are eight articles suitable for the criteria. Four articles were research conducted in China, and four articles were done in the United States. The articles use case series, cohort, and cross-sectional methods. Conclusion: Common comorbidities among COVID-19 patients are hypertension, diabetes, and cardiovascular disease in China and the United States. A more significant number of comorbidities also correlated with a higher risk of death.